Ultra-Orthodox Israeli men break a taboo by working. - Chabin, Michele (Christian Century, 2016)
The article discusses a trend among ultra-Orthodox or Haredi Jewish men in Israel to find employment rather than study sacred texts. Topics include the work of the government-funded Bnei Brak Employment Center in providing job training to Haredi Jews, the ability of ultra-Orthodox Jews to do computer programming in relation to the study of religious texts, and the employment of Haredi women.